2015
DOI: 10.1007/s10902-015-9658-0
|View full text |Cite
|
Sign up to set email alerts
|

Circles of Happiness: Students’ Perceptions of Bidirectional Crossovers of Subjective Well-Being

Abstract: The mental well-being of the world's adolescents has decreased in the last 20-30 years. Such a trend is visible also in Sweden, a country otherwise considered a positive example in terms of child well-being. In Sweden, students in lower secondary school are especially exposed. From a salutogenic orientation, this study qualitatively explored 200 Swedish students' (grades 5-9) perceptions of the role of happiness in school. Students perceived happiness as both promoting and being promoted by five aspects: learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…Holopainen et al (2012) suggested that adolescents' psychological well-being can positively predict their cooperation skills. Other studies found the phenomenon of "Circles of Happiness," pointing out that individual happiness and prosocial behaviors can mutually promote each other (Aknin et al, 2012;Backman, 2016). Happiness will promote individuals to make more prosocial behaviors, and prosocial behaviors will enhance individuals' happiness experience.…”
Section: Relationship Between Life Satisfaction and Prosocial Behavmentioning
confidence: 99%
“…Holopainen et al (2012) suggested that adolescents' psychological well-being can positively predict their cooperation skills. Other studies found the phenomenon of "Circles of Happiness," pointing out that individual happiness and prosocial behaviors can mutually promote each other (Aknin et al, 2012;Backman, 2016). Happiness will promote individuals to make more prosocial behaviors, and prosocial behaviors will enhance individuals' happiness experience.…”
Section: Relationship Between Life Satisfaction and Prosocial Behavmentioning
confidence: 99%
“…The search was conducted in 2018 using the Boolean criteria wherein the term "happiness" is used synonymously with subjective well-being (SWB), life satisfaction, well-being, and welfare as evident in the previous works [28][29][30][31][32]. The search query resulted in an initial list of 411 papers out of which 218 were finally selected, as depicted in Figure 2.…”
Section: Planning and Conducting The Reviewmentioning
confidence: 99%
“…(2010) study of 12‐ to 13‐year olds that family and friends were integral to their happiness. Chaplin's (2009) investigation into what makes children and adolescents happy revealed five themes: people and pets, achievements, material things, hobbies and sports, and Backman's (2016) study showed that young people associated happiness with relationships, positive behaviours and school learning.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring young people's well‐being in this way does not allow young people's own points of view on their subjective well‐being to be heard or considered (Backman, 2016; Garcia & Sikström, 2013; Vujčić et al., 2019). Within Psychology, the tendency to adopt adult constructed measurements to investigate the meanings children attribute to thinking about themselves (e.g.…”
Section: Conceptualising Happinessmentioning
confidence: 99%
See 1 more Smart Citation